Comparative Transcriptomics of Steinernema and Caenorhabditis Single Embryos Reveals Orthologous Gene Expression Convergence during Late Embryogenesis. (27th September 2017) - Macchietto, Marissa; Angdembey, Dristi; Heidarpour, Negar; Serra, Lorrayne; Rodriguez, Bryan; El-Ali, Nicole; Mortazavi, Ali
Abstract: Cells express distinct sets of genes in a precise spatio-temporal manner during embryonic development. There is a wealth of information on the deterministic embryonic development of Caenorhabditis elegans, but much less is known about embryonic development in nematodes from other taxa, especially at the molecular level. We are interested in insect pathogenic nematodes from the genus Steinernema as models of parasitism and symbiosis as well as a satellite model for evolution in comparison to C. elegans . To explore gene expression differences across taxa, we sequenced the transcriptomes of single embryos of two Steinernema species and two Caenorhabditis species at 11 stages during embryonic development and found several interesting features. Our findings show that zygotic transcription initiates at different developmental stages in each species, with the Steinernema species initiating transcription earlier than Caenorhabditis . We found that ortholog expression conservation during development is higher at the later embryonic stages than at the earlier ones. The surprisingly higher conservation of orthologous gene expression in later embryonic stages strongly suggests a funnel-shaped model of embryonic developmental gene expression divergence in nematodes. This work provides novel insight into embryonic development across distantly related nematode species and demonstrates that the mechanisms controlling early development are more diverse than previously thought at the transcriptional level.